2015
DOI: 10.3892/ol.2015.3857
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MCPH1 inhibits uncontrolled cell growth by promoting cell apoptosis and arresting the cell cycle in S and G2/M phase in lung cancer cells

Abstract: Abstract. Microcephalin (MCPH1/BRIT1) is a large nuclear protein that is involved in the early cellular response to DNA damage, the expression of which is reduced in a variety of types of human tumors. A recent study by our group demonstrated that MCPH1 expression is markedly decreased in lung cancer. However, it remains unclear whether inducing the expression of MCPH1 may ameliorate lung cancer, and, if so, which mechanisms underlie this process. The results of the present study demonstrated that MCPH1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…However, it is unclear how a sustained expression of MCPH1 is toxic to cells. It is interesting to note two recent publications showing that the overexpression of MCPH1 inhibits cell proliferation by promoting apoptosis (Zhou et al , ) and activating the cytochrome c‐caspase 3 signaling (Mai et al , ). The ubiquitination of MCPH1 is realized by a direct interaction of MCPH1 with Cdh1 and also possibly by an interaction with the scaffold component Cdc27 of APC/C (Singh et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear how a sustained expression of MCPH1 is toxic to cells. It is interesting to note two recent publications showing that the overexpression of MCPH1 inhibits cell proliferation by promoting apoptosis (Zhou et al , ) and activating the cytochrome c‐caspase 3 signaling (Mai et al , ). The ubiquitination of MCPH1 is realized by a direct interaction of MCPH1 with Cdh1 and also possibly by an interaction with the scaffold component Cdc27 of APC/C (Singh et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The main property of tumor cells is uncontrollable cell growth, and the cell cycle arresting becomes a pivotal therapy target in remedies. 21 The above studies showed that SSMO-5 can induce apoptosis; therefore, the effect of SSMO-5 on the cell cycle was investigated by ow cytometry (Fig. 3).…”
Section: Ssmo-5-induced Cell Cycle Arresting In Nci-h446 Cellsmentioning
confidence: 99%
“…The MCPH1 gene, also known as BRIT1 , has been shown to be associated with autosomal recessive primary microcephaly (Jackson et al, ). Overexpression of the MCPH1 gene has been reported to inhibit uncontrolled lung cancer cell growth by promoting cell apoptosis and arresting the cell cycle in S and G2/M phase (Zhou et al, ). Here, we have found that overexpression of a clone containing the reference MCPH1 sequence led to a decrease in cell counts.…”
Section: Discussionmentioning
confidence: 99%